Petunia PLEIOTROPIC DRUG RESISTANCE 1 Is a Strigolactone Short-Distance Transporter with Long-Distance Outcomes. (10th May 2019) - Shiratake, Katsuhiro; Notaguchi, Michitaka; Makino, Haruko; Sawai, Yu; Borghi, Lorenzo
Abstract: Phytohormones of the strigolactone (SL) family have been characterized as negative regulators of lateral bud outgrowth and triggers of symbioses between plants and mycorrhizal fungi. SLs and their precursors are synthesized in root tips as well as along shoot and root vasculature; they either move shoot-wards and regulate plant architecture or are exuded from roots into the soil to establish mycorrhizal symbiosis. Owing to the difficulty in quantification of SL in shoot tissues because of low abundance, it is not yet clear how SL distribution in plants is regulated at short- and long-distances from SL biosynthetic and target tissues. To address this question, we grafted wild-type scions and rootstocks from different petunia mutants for SL biosynthesis/transport and investigated SL activity by quantifying lateral bud outgrowth in the main shoot. Based on these results, we show that (i) the previously reported petunia SL transporter PLEIOTROPIC DRUG RESISTANCE 1 (PDR1) directly accounts for short-distance SL transport and (ii) long-distance transport of SLs seems to be partially and not directly dependent on PDR1. These data suggest that the root-to-shoot transport of SLs occurs either via the vasculature bundle through transporters other than PDR1 or involves SL precursors that are not substrates of PDR1.